An Empirical Examination of the Impact of Economic Structural Change on Income Inequality: Dynamic Heterogeneous Panel Approach - Elhini, Maha; Hammam, Rasha (European Journal of Sustainable Development, 2021)
This paper employs structural growth perspective to the analysis of income inequality in 43 countries over the period 2003-2017.The study utilizes two different panel estimation techniques. First, the panel least squares regression examines the relevance of Kuznets effect of the different economic sectors; agriculture, manufacturing and services on income inequality. Second, the pooled mean group (PMG) estimation of dynamic heterogeneous panels gauges the long run impact of the change in sectoral value added as a proxy for structural change on inequality. PMG presents short run adjustments to be country-specific due to the widely different impacts of macroeconomic conditions and vulnerability of each country to income inequality. Empirical findings show that across all countries, sector growth had no to negligible impact on inequality indicating that no signs are evident of Kuznets effect. However, both inflation and unemployment have mixed impacts on inequality in Lower and Middle-Income countries. Results further reveal that unemployment has a relatively stronger influence on inequality than inflation for Upper-middle income countries, unlike in Lower-middle income countries, where unemployment shows a weaker correlation with inequality than inflation. Results for High-income countries show that the influence between inflation and unemployment are not as big as in Upper middle-income countries.